10-year outcomes in localized prostate cancer: Authors' reply - Hamdy, F; Donovan, J; Neal, D (Massachusetts Medical Society, 2017)
We agree with Klotz and Kibel that the lack of significant differences in survival among the three treatments makes a comparison between radiotherapy and surgery unwise. The predetermined power calculation for the ProtecT trial estimated a prostate-cancer mortality rate of 10% at a median of 10 years, and because the observed rate was 1%, longer follow-up is required to evaluate differences. We agree that the ProtecT findings should not be interpreted as a case against active surveillance. The similar rates of survival in the three groups, the lower rate of symptoms in the active-monitoring group than in the radical-treatment groups, and the finding that 80% of the men in the active-monitoring group remained progression- free provide evidence to support this option.